2019
DOI: 10.1177/2055668319863557
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the use of robotic and virtual reality rehabilitation technologies to improve function in stroke survivors: A narrative review

Abstract: This review evaluates the effectiveness of robotic and virtual reality technologies used for neurological rehabilitation in stroke survivors. It examines each rehabilitation technology in turn before considering combinations of these technologies and the complexities of rehabilitation outcome assessment. There is high-quality evidence that upper-limb robotic rehabilitation technologies improve movement, strength and activities of daily living, whilst the evidence for robotic lower-limb rehabilitation is curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 53 publications
0
46
0
Order By: Relevance
“…We compared our research with the most similar studies performed in the last 6 years for VR- and robotics-based lower limb rehabilitation (Lee et al, 2014 ; Xiang et al, 2014 ; Givon et al, 2015 ; Ko et al, 2015 ; Song and Park, 2015 ; Gibbons et al, 2016 ; Lo et al, 2017 ; Darbois et al, 2018 ; Clark et al, 2019 ). These studies used the same clinical scales to measure the rehabilitation progress of lower limb function and/or were performed in the acute period of ischemic stroke.…”
Section: Discussion Conclusion and Further Workmentioning
confidence: 99%
“…We compared our research with the most similar studies performed in the last 6 years for VR- and robotics-based lower limb rehabilitation (Lee et al, 2014 ; Xiang et al, 2014 ; Givon et al, 2015 ; Ko et al, 2015 ; Song and Park, 2015 ; Gibbons et al, 2016 ; Lo et al, 2017 ; Darbois et al, 2018 ; Clark et al, 2019 ). These studies used the same clinical scales to measure the rehabilitation progress of lower limb function and/or were performed in the acute period of ischemic stroke.…”
Section: Discussion Conclusion and Further Workmentioning
confidence: 99%
“…Very few studies ( 25 , 26 ) have attempted to assess the additional benefits of this combination of technologies. Patients #1 and #5 in our study showed marginal motor improvements on the FM UE scale ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…The main objective of rehabilitation technologies is to maintain or improve the functioning and independence of an individual, in addition to facilitating participation and improving general well-being. 10 In the last decade, the use of technological devices in the rehabilitation of patients affected by stroke has increased, which are developed to improve stroke results, due to the increase in intensity, repetitions, specificity and feedback during rehabilitation. 10,11 There is a wide range of technologies with applications in rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…10 In the last decade, the use of technological devices in the rehabilitation of patients affected by stroke has increased, which are developed to improve stroke results, due to the increase in intensity, repetitions, specificity and feedback during rehabilitation. 10,11 There is a wide range of technologies with applications in rehabilitation. Iosa conducts a review describing the “Seven capital devices for the future of Stroke rehabilitation”: robots, brain computer interfaces, neuroprostheses, non-invasive brain stimulators, wearable devices, virtual reality and tablet-pc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation